Analisis Dampak Gadget Pada Perkembangan Sosial Anak di SD Negeri Limbangan Wetan 02 - Widya Ulmi; Moh Toharudin; Muamar Muamar (Jurnal Ilmiah Wahana Pendidikan, 2022)
The background of this study is based on the impact of using gadgets on the social development of children at SDN Limbangan Wetan 02. The purpose of this study was to determine the impact of gadgets on the social development of children at SDN Limbangan Wetan 02, Brebes district. This type of research uses descriptive qualitative research, while the data collection techniques used are interviews, observations, and documentation directly with informants in the field to obtain the required data. Data analysis in this study used data analysis techniques using the Miles and Huberman flow model, namely data reduction, data presentation, and conclusion drawing or verification to determine the impact of using gadgets on the social development of children at SDN Limbangan Wetan 02 Brebes sub-district. The conclusion of this researcher is that there is a negative impact of gadgets on the social development of children at SDN Limbangan Wetan 02, Brebes sub-district. This impact is caused because children use it too often at home without being controlled by their parents and children who are addicted to using gadgets feel that gadgets are the most interesting thing than playing with people around or their peers. Therefore, schools are expected to always provide activities that are able to stimulate children's social development when they are in the school environment. Then parents are expected to be able to control and supervise children when using gadgets at home.